Recommendations for assessing cognitive risks in young children treated for ependymoma for clinical and research protocols: evidence from a systematic literature review - Morrall, Matthew C.H.J.; Pitchford, Nicola J.; Waters, Emma C.; Ablett, Kate L.; Stocks, Helen; Walker, David; Grundy, Richard G. (Pharma Publisher, 2014)
Background: Current treatment approaches for pediatric ependymoma differ between North American and European studies. Post-surgical adjuvant irradiation is used in children aged <36 months in North America, whilst European approaches use chemotherapy to avoid or defer radiotherapy until three years of age, in order to avoid late neurocognitive toxicity. To establish evidence for the effects of cranial radiotherapy in children aged <36 months with ependymoma on neurocognitive outcomes, we conducted a systematic literature review assessing methodological approaches for measuring neurocognitive outcome. Methods: Eight databases were selected to perform an advanced search, retrieval and systematic review of papers describing neurocognitive outcome in children diagnosed with ependymoma who received cranial radiotherapy at <36 months. Results: Limitations of published data permitted descriptive analysis only. Considerable variation in reporting survival rates, techniques and timing of psychometric testing and the results of neurocognitive outcomes was identified. Conclusions: The review identified significant inconsistencies of neurocognitive testing, particularly literacy skills, developmental time points for testing and methods of data reporting. The role of the cerebellum for cognitive development, especially reading, has been inadequately evaluated in published studies. Recommendations are made to improve assessment methods, and time points for testing, so that reports do not fail to identify children who acquire deficits as they mature through childhood and adolescence. We conclude that claims that radiation treatment for ependymoma administered aged <36 months is associated with limited neurocognitive consequences, are not supported by the literature.